Long-term follow-up of thumb reconstruction with a heterotopic replanted finger: case report and literature review - Ma, Zhihu; Zhang, Xingsheng; Wang, Gang; Zhu, Lei; Pei, Yantao; Sun, Yuliang; Liu, Ben (Frontiers in Bioengineering and Biotechnology, 2024)
Objectives This work aimed to study the long-term outcome and function of a heterotopic replanted finger. Methods Retrospective analysis of two cases of successful finger reconstruction after finger heterotopic replantation. One case was a severed thumb, and the other case was a severed finger. The average follow-up time was 10 years. The clinical outcome and function of the heterotopic replanted finger, including range of motion, grip strength, and sensory recovery, were analyzed,. A comparative analysis was conducted with patients who underwent thumb replantation in the same period. Results The two heterotopically replanted fingers survived. Five months after the heterotopic replantation surgery, a new thumb was reconstructed using the heterotopically replanted thumb and the free tarsometatarsal joint from the foot. In the other case, the finger was reconstructed 1 year later with a free anterolateral thigh flap and the heterotopically replanted finger. The movement of the thumb, the pinching of the fingers, the clenching of the fist, and the feeling recovery were all good. The patient was capable of independently performing daily life and work activities such as eating, dressing, writing, and so on. There was no significant difference in hand function between the patients who received in situ finger replantation and heterotopic replantation during the same period. Conclusion For severed fingers that cannot be replanted in situ in an emergency situation, heterotopic replantation and secondary reconstruction may be a feasible and practical surgical method.